The Effectiveness of Police Personnel Expenditure Budget Management from the Perspective of Government Financial Accountability - I Gede Wiradana; Erham; Musmuliadin (Lembaga Bale Literasi, 2025)
The management of the state budget within the Indonesian National Police is an integral part of the state financial system that must be carried out based on the principles of accountability, effectiveness, efficiency, transparency, and legal certainty. In practice, the management of personnel expenditure budgets at the district police level still faces various obstacles that prevent the organization from fully achieving its objectives. This study aims to analyze the effectiveness of personnel expenditure budget management, the evaluation mechanisms applied, and the factors influencing the effectiveness of budget management at the Panda District Police. The study employs a qualitative descriptive approach with data collection through observation, interviews, documentation, and literature review. Data analysis was conducted interactively through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the budget management system has complied with the provisions of laws and regulations regarding state finances; however, the effectiveness of its implementation is still influenced by limited budget allocations, changes in operational needs, planning mechanisms that are not yet fully based on actual needs, and an evaluation process that has not been able to prevent recurring budget deficits. This study proposes strengthening a performance-based budget management model through the optimization of planning, internal oversight, and continuous evaluation as an effort to enhance state financial accountability in the performance of police functions.